The Effect of Additional Employee Income on the Performance of State Civil Apparatus at the Regional Research and Innovation Agency of Central Sulawesi Province - Haris Abd Kadir; Awaluddin; Abdul Rahman (Universitas Muhammadiyah Palu, 2025)
This study aims to analyse the effect of work productivity and work discipline on employee performance at the Regional Research and Innovation Agency of Central Sulawesi Province. The research method uses a quantitative approach with multiple linear regression analysis. The research sample amounted to 48 respondents. The results showed that simultaneously work productivity and work discipline had a significant effect on employee performance with an F-count value of 22,114 and a significance of 0.000. Partially, work productivity has a positive and significant effect on employee performance with a regression coefficient of 1.077 and a significance of 0.022. The work discipline variable also has a positive and significant effect on employee performance with a regression coefficient of 1.853 and a significance of 0.003. . The R-square value of 0.496 indicates that the work productivity and work discipline variables are able to explain the variation in employee performance by 49.6%, while the remaining 50.4% is explained by other variables not studied. This research makes an important contribution to the development of human resource management in the public sector, especially in efforts to improve employee performance through optimising productivity and work discipline.